Pomembnost porfirinov v laboratorijski diagnostiki - Krnjak, Ljuba (Farmacevtski vestnik, 2005)
Porphyrins are cyclic tetrapyrroles which can be considered as derivatives of the parent tetrapyrrole. They are synthesized in all mammalian cells. They excrete of the health human body in small quantities through excrement and urinous. In humans, there are three major porphyrinsČ uroporphyrin, coproporphyrin and protopotphyrin. Porphyrias are hereditary or acquired disorders of heme biosynthesis. For practical reasons, they are classified into erythropoietic or hepatic forms according to the primary site of enzyme deficiency. For the clinical manifestation of hepatic porphyrias secondary factors are usually of importance, e.g. drugs, hormones, nutrition, alcohol, certain halogenated hydrocarbon compounds, hepatic lesions. Acute hepatic porphyrias have to give rise to medical emergencies and require intensive care treatment.
Keywords: laboratorijska diagnostika; porfirija; porfirini